Re-shaping hysteretic behaviour?spectral analysis and design equations for semi-active structures. - Rodgers, Geoffrey W.
Semi-active dampers offer significant capability to reduce dynamic wind and seismic structural response. A novel resetable device with independent valve control laws that enables semi-active re-shaping of the overall structural hysteretic behaviour has been recently developed, and a one-fifth scale prototype experimentally validated. This research statistically analyses three methods of re-shaping structural hysteretic dynamics in a performance-based seismic design context. Displacement, structural force, and total base-shear response reduction factor spectra are obtained for suites of ground motions from the SAC project. Results indicate that the reduction factors are suite invariant. Resisting all motion adds damping in all four quadrants and showed 40?60% reductions in the structural force and displacement at the cost of a 20?60% increase in total base-shear. Resisting only motion away from equilibrium adds damping in quadrants 1 and 3, and provides reductions of 20?40%, with a 20?50% increase in total base-shear. However, only resisting motion towards equilibrium adds damping in quadrants 2 and 4 only, for which the structural responses and total base-shear are reduced 20?40%. The spectral analysis results are used to create empirical reduction factor equations suitable for use in performance based design methods, creating an avenue for designing these devices into structural applications. Overall, the reductions in both response and base-shear indicate the potential appeal of this semi-active hysteresis sculpting approach for seismic retrofit applications?largely due to the reduction of the structural force and overturning demands on the foundation system.
Keywords: Hysteretic behaviour; Structural design; Response spectra; Semi-active control; Reduction factors